Phonological awareness in reading : (Springer-Verlag, 1990)
In this volumume prominent scholars from different cultural and linguistic backgrounds are brought together to review the empirical studies on the ability to reflect upon and manipulate the phonemic segments of speech, and to present their insights on the relationship of phonological aware- ness to the reading process.